Fathers and daughters - Sharpe, Sue, 1945- (Male orders., 1994)
Sharpe explores important factors in the relationships between fathers and daughters. She uses the words and experiences of fathers and daughters to draw out the complexities, conflicts and contradictions of this unique relationship.